Outcome of treatment seeking rural gamblers attending a nurse-led cognitive-behaviour therapy service: A pilot study - Barry Tolchard (Elsevier, 2016)
Objectives: Little is known about the differences between urban and rural gamblers in Australia, in terms of comorbidity and treatment outcome. Health disparities exist between urban and rural areas in terms of accessibility, availability, and acceptability of treatment programs for problem gamblers. However, evidence supporting cognitive-behaviour therapy as the main treatment for problem gamblers is strong. This pilot study aimed to assess the outcome of a Cognitive-Behavioural Therapy (CBT) treatment program offered to urban and rural treatment-seeking gamblers. Methods: People who presented for treatment at a nurse-led Cognitive-Behavioural Therapy (CBT) gambling treatment service were invited to take part in this study. A standardised clinical assessment and treatment service was provided to all participants. A series of validated questionnaires were given to all participants at (a) assessment, (b) discharge, (c) at a one-month, and (d) at a 3-month follow-up visit. Results: Differences emerged between urban and rural treatment-seeking gamblers. While overall treatment outcomes were much the same at three months after treatment, rural gamblers appeared to respond more rapidly and to have sustained improvements over time. Conclusion: This study suggests that rural problem gamblers experience different levels of co-morbid anxiety and depression from their urban counterparts, but once in treatment appear to respond quicker. ACBT approach was found to be effective in treating rural gamblers and outcomes were maintained. Ensuring better availability and access to such treatment in rural areas is important. Nurses are in a position as the majority health professional in rural areas to provide such help. Keywords: Evidence based health care, Health program evaluation, Models of care, Rural health services delivery, Rural mental health